2022
DOI: 10.3389/fmicb.2022.845563
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles of the Rotary Type 9 Secretion System

Abstract: The Fo ATP synthase, the bacterial flagellar motor, and the bacterial type 9 secretion system (T9SS) are the three known proton motive force driven biological rotary motors. In this review, we summarize the current information on the nuts and bolts of T9SS. Torque generation by T9SS, its role in gliding motility of bacteria, and the mechanism via which a T9SS-driven swarm shapes the microbiota are discussed. The knowledge gaps in our current understanding of the T9SS machinery are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 103 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…Highly active genes within this transcriptome belong to T9SS mechanism and gliding motility ( Supplementary Table S4 ). Overall, 18 genes ( gldA , gldB , gldD , gldF , gldG , gldH , gldI , gldJ , gldK , gldL , gldM , gldN , sprA , sprE , sprF , sprT , porU and porV ), required for gliding motility and protein secretion, and/or involved in T9SS ( Hunnicutt and Mcbride, 2000 ; McBride and Braun, 2004 ; Braun et al, 2005 ; Lauber et al, 2018 ; McBride, 2019 ; Hennell James et al, 2021 ; Trivedi et al 2022 ; Veith et al, 2022 ), were identified among DEGs ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Highly active genes within this transcriptome belong to T9SS mechanism and gliding motility ( Supplementary Table S4 ). Overall, 18 genes ( gldA , gldB , gldD , gldF , gldG , gldH , gldI , gldJ , gldK , gldL , gldM , gldN , sprA , sprE , sprF , sprT , porU and porV ), required for gliding motility and protein secretion, and/or involved in T9SS ( Hunnicutt and Mcbride, 2000 ; McBride and Braun, 2004 ; Braun et al, 2005 ; Lauber et al, 2018 ; McBride, 2019 ; Hennell James et al, 2021 ; Trivedi et al 2022 ; Veith et al, 2022 ), were identified among DEGs ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo orientation measurement through single-molecule polarization microscopy (Shroder et al, 2016) of fluorescently labeled proteins is another possible approach to circumvent the difficulty of labeling periplasmic proteins with microparticles. The Bacteroidetes gliding system is reviewed elsewhere in this collection (Trivedi et al, 2022).…”
Section: Gldlm Bacteroidetes Gliding Systemmentioning
confidence: 99%
“…One possibility is that the rotating motor pushes on a tread carrying SprB filaments and propels it along the helical GldJ track 4 , 24 . Alternatively, the SprB filaments could be anchored on the tracks, and the tracks could be propelled by the motor 24 , 58 .…”
Section: Discussionmentioning
confidence: 99%